A nested autoencoder approach to automated defect inspection on textured surfaces - Oz, Muhammed Ali Nur; Kaymakci, Ozgur Turay; Mercimek, Muharrem (Zielona Góra: Uniwersytet Zielonogórski)
In recent years, there has been a highly competitive pressure on industrial production. To keep ahead of the competition, emerging technologies must be developed and incorporated. Automated visual inspection systems, which improve the overall mass production quantity and quality in lines, are crucial. The modifications of the inspection system involve excessive time and money costs. Therefore, these systems should be flexible in terms of fulfilling the changing requirements of high capacity production support.
Keywords: autoencoders; defect detection; automatic visual inspection; deep learning